ZIKA VIRUS SERENE PROTEASE COMPLEX (NS2B-NS3) INHIBITION BY 2-AMINO-5-{[(1Z)-AMINO({[(Z)-BENZOYL]IMINO})METHYL]AMINO}-N-(5-AMINO-7-{[CARBAMOYL(PHENYL)METHYL]AMINO}-6-OXOHEPTYL)PENTANAMIDE, IN SILICO STUDIES - Singh, Kalpana Virendra; Merugu, Ramchander; Solanki, Jeeven Singh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The present in silico study is taken to report 2-amino-5-{[(1Z) -amino ({[(Z) -benzoyl] imino}) methyl] amino} -N-(5-amino-7-{[carbamoyl (phenyl) methyl] amino} -6-oxoheptyl) pentanamide as Zika virus (ZIKV) NS2B-NS3 protease inhibitor. Methods: In silico studies performed on online docking servers. NS2B-NS3 serine protease from ZIKV with PDB ID: 5GJ4 a hydrolase with total structure weight of 102878.54 is selected as the target. Docking server is used for carrying out docking calculations. Lamarckian genetic algorithm and the Solis and Wets local search methods are used for performing docking simulations. Free energy calculations, hydrogen bond (HB) formation, polar and hydrophobic interactions and HB plot are studied in this study. Results: Binding pocket is found on a serine protease NS2B chain A. Binding site predictions propose NKK as the suitable ligand for binding, which has structure closely related to the proposed ligand2-amino-5-{[(1Z) -amino ({[(Z) -benzoyl] imino}) methyl] amino} -N-(5-amino-7-{[carbamoyl (phenyl) methyl] amino} -6-oxoheptyl) pentanamide. Free energy of binding is - 4.08 kcal/Mol and inhibition constant (Ki) is very less 1.02 mm. The ligand binds to chain A of NS2B and chain B of NS3 serine protease. The legend is bound to serine protease complex through strong HB, formed between THR 60 (A) and N6 of ligand, GLU62 (A) and N8 of ligand, ARG 55 (A) and N3 of ligand and ASN108 (B) and N7 of ligand apart from polar and hydrophobic interactions. Conclusion: Docking studies performed establishes the proposed ligand2-amino-5-{[(1Z)-amino ({[(Z)-benzoyl] imino}) methyl] amino} -N-(5- amino-7-{[carbamoyl (phenyl) methyl] amino}-6-oxoheptyl) pentanamide as a molecule which can be used for the inhibition of ZIKV NS2B-NS3 serine protease. Â Â 